2022
DOI: 10.1515/jpem-2021-0591
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sports participation on components of metabolic syndrome in adolescents: ABCD growth study

Abstract: Objectives This study aimed to analyze the impact of sports participation (12 months of practice) on the components of metabolic syndrome (MetS) in both sexes. Methods This is an observational longitudinal study, a part of which is entitled “Analysis of Behaviors of Children During Growth” (ABCD Growth Study), Presidente Prudente, São Paulo, Brazil. The sample was composed of 171 adolescents (112 boys and 59 girls), divided i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
0
1
0
Order By: Relevance
“…In fact, a recent meta-analysis [ 3 ] showed that children and adolescents who participate in sports present better cardiovascular structure and function compared to those who do not participate, such as lower blood pressure values and carotid intimal thickness. In addition, original studies have shown that participation in sports is associated with better glucose values [ 4 ] and heart rate variability [ 5 ], dyslipidemias [ 6 , 7 ], and cardiac autonomic modulation [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, a recent meta-analysis [ 3 ] showed that children and adolescents who participate in sports present better cardiovascular structure and function compared to those who do not participate, such as lower blood pressure values and carotid intimal thickness. In addition, original studies have shown that participation in sports is associated with better glucose values [ 4 ] and heart rate variability [ 5 ], dyslipidemias [ 6 , 7 ], and cardiac autonomic modulation [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The effort to overcome BMI and high cholesterol due to obesity is to do a low-carbohydrate diet (Pour Abbasi et al, 2022) as well as do regular exercise. Exercise can protect adults from having metabolic syndrome (Menezes et al, 2022). The incidence of stroke can be reduced by avoiding hypertension, smoking, diabetes mellitus, obesity, dyslipidemia, and lack of activity (Agianto, Yulise, Agustina, & Rizany, 2023).…”
Section: Introductionmentioning
confidence: 99%